A toolbox for a structured risk-based prehabilitation program in major surgical oncology - Sliwinski, Svenja; Werneburg, Elisabeth; Faqar-Uz-Zaman, Sara Fatima; Detemble, Charlotte; Dreilich, Julia; Mohr, Lisa; Zmuc, Dora; Beyer, Katharina; Bechstein, Wolf O.; Herrle, Florian; Malkomes, Patrizia; Reissfelder, Christoph; et al. (Frontiers in Surgery, 2023)
Prehabilitation is a multimodal concept to improve functional capability prior to surgery, so the patients’ resilience is strengthened to withstand any peri- and postoperative comorbidity. It covers physical activities, nutrition, and psychosocial well-being. The literature is heterogeneous in outcomes and definitions. In this scoping review, class 1 and 2 evidence was included to identify 7 main aspects of prehabilitation for treatment pathway: i) risk assessment, ii) FITT (frequency, interventions, time, type of exercise)-principles of prehabilitation exercise, iii) outcome measures, iv) nutrition, v) patient blood management vi), mental well-being, and vii) economic potential. Recommendations include the risk of tumor progression due to delay of surgery. Patients undergoing prehabilitation should perceive risk assessment by structured, quantifiable, and validated tools like RAI, Charlson Comorbidity Index, ASA, or ECOG scoring. Assessments should be repeated to quantify its effects. The most common types of exercise include breathing exercises and moderate to high-intensity interval protocols. The program should have a duration of 3 to 6 weeks with 3 to 4 exercises per week that take 30 to 60 minutes. The 6-MWT is a valid and resource-saving tool to assess changes in aerobic capacity. Long-term assessment should include standardized outcome measurements (overall survival, 90-day survival, Dindo-Clavien/CCI®) to monitor the potential of up to 50% less morbidity. Finally, individual cost-revenue assessment can help to assess health economics, confirming the hypothetic saving of $8 for treatment for $1 spent for prehabilitation. These recommendations should serve as toolbox to generate hypotheses, discussion, and systematic approaches to develop clinical prehabilitation standards.